2021
DOI: 10.1101/2021.12.14.472599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short prokaryotic Argonautes provide defence against incoming mobile genetic elements through NAD+ depletion

Abstract: Argonaute (Ago) proteins are found in all three domains of life. The so-called long Agos are composed of four major domains (N, PAZ, MID, and PIWI) and contribute to RNA silencing in eukaryotes (eAgos) or defence against invading mobile genetic elements in prokaryotes (pAgos). Intriguingly, the majority (~60%) of prokaryotic Agos (pAgos) identified bioinformatically are shorter (comprised of only MID and PIWI domains) and are typically associated with Sir2, Mrr or TIR domain-containing proteins. The cellular f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 82 publications
2
17
0
Order By: Relevance
“…For example, the Cap4 endonuclease functions as the effector domain in CBASS systems, where it cleaves both host and phage DNA when activated (Lowey et al, 2020). Moreover, SIR2 domains cause NAD + depletion in many abortive infection systems, including Thoeris, DSR, and more (Garb et al, 2021; Ofir et al, 2021; Zaremba et al, 2021). It is therefore likely that systems in the Lamassu family all protect against phage via abortive infection.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the Cap4 endonuclease functions as the effector domain in CBASS systems, where it cleaves both host and phage DNA when activated (Lowey et al, 2020). Moreover, SIR2 domains cause NAD + depletion in many abortive infection systems, including Thoeris, DSR, and more (Garb et al, 2021; Ofir et al, 2021; Zaremba et al, 2021). It is therefore likely that systems in the Lamassu family all protect against phage via abortive infection.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies over the past few years have revealed a plethora of additional defense mechanisms commonly employed by bacteria. These include phage restriction by prokaryotic Argonaute proteins (Garb et al, 2021; Koopal et al, 2022; Kuzmenko et al, 2020; Zaremba et al, 2021), production of small molecules that block phage propagation (Bernheim et al, 2021; Kever et al, 2022; Kronheim et al, 2018), depletion of molecules essential for phage replication (Garb et al, 2021; Hsueh et al, 2022; Ofir et al, 2021; Tal et al, 2022), systems that use small molecule signaling to activate immune effectors (Cohen et al, 2019; Ofir et al, 2021; Tal et al, 2021; Whiteley et al, 2019), retrons that involve reverse transcription of non-coding RNAs (Bobonis et al, 2022; Gao et al, 2020; Millman et al, 2020), and more (Doron et al, 2018; Gao et al, 2020; Goldfarb et al, 2015; Johnson et al, 2022; Millman et al, 2022; Ofir et al, 2018; Rousset et al, 2022; Vassallo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Short pAgos are inactive as a result of the mutation of the catalytic tetrad, and their functions have been a mystery for a long time until most recently. It was reported that short pAgos and a (preduso)short pAgo from Sulfolobus islandicus (Si) constitute defense systems together with their associated proteins [20][21][22][23][24] . These short pAgos systems confer immunity against viruses and plasmids via an abortive infection (Abi) response 25 , a defense strategy kills the infected cells or induces cell dormancy to suppress the spreading of the invaders 26 .…”
Section: Introductionmentioning
confidence: 99%